(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, the unit of thought and the linguistic realization of the concept, which arises as a mental phenomenon, are also the result of speech and thought activity, and highlights some studies related to the interpretation of the concept in Uzbek linguistics.